Feminist critique of representation and gender as a universal category: Field of disputes (TEL Tempo, Espaço e Linguagem, 2023)
The purpose of this essay is to establish a bibliographical discussion about feminism in the contexts of theories of modernity and postmodernity, focusing on the critique of the homogenization of the subjects of the feminist movement, as a strategy to mobilize political force. Not less important, I also establish a discussion about gender, questioning its unrestricted applicability to all societies and ethnic groups, in addition to making a comparison between racialized and white women in relation to marriage and motherhood, which have established themselves as two great myths related to the “biological and social destiny” of women.